Analisis Efektivitas Mesin Stone Crusher Dengan Menggunakan Metode Overall Equipment Effectiveness (OEE) Pada PT.Vira Jaya Riau Putra - Hendri Yanto; Dodi Sofyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This study aims to analyze the production process on Stone Crusher machine using the Overall Equipment Effectiveness method at PT Vira Jaya Riau Putra. From the OEE calculation result, it is found that OEE value of Stone Crusher machine of 64,71% is still below world class standart of OEE (85%). The low value of OEE is caused by one of the factors such as the machine availability, which more stand by for raw material to be processed again. From the analysis of big losses that most significantly affect the low value of OEE Stone Crusher machine that is reduced speed loss, setup and adjustment losses. The reduced speed loss is caused by the decrease in production speeds made by the operator and the high setup and adjustment losses due to the engine being left idle due to the low performance of the Stone Crusher engine to produce products that match the desired results.Keywords: OEE, Stone Crusher, Six Big Losses